A 24‐channel shim array for the human spinal cord: Design, evaluation, and application. Issue 5 (4th August 2016) - Topfer, Ryan; Starewicz, Piotr; Lo, Kai‐Ming; Metzemaekers, Karl; Jette, Donald; Hetherington, Hoby P.; Stikov, Nikola; Cohen‐Adad, Julien
Abstract : Purpose: A novel multichannel shim array is introduced to improve MRI and spectroscopic studies of the human spinal cord. Methods: Twenty‐four–channel shim and 8‐channel transceiver arrays were designed to insert into the patient bed table to lie in close proximity to the subject's spine. The reference field patterns of each of the shim channels (Hz/A) were determined empirically via gradient echo field mapping and subsequently used to demonstrate shim performance at 3 Tesla using an ex vivo phantom, which incorporated a fixed human spine. The shim was further demonstrated on five healthy volunteers. Results: Application of the shim to the ex vivo phantom reduced the standard deviation of the field over the spinal volume of interest (123.4 cm 3 ) from an original 51.3 Hz down to 32.5 Hz, amounting to an improvement in field homogeneity of 36.6%. In vivo, the spine shim resulted in an average improvement in field homogeneity of 63.8 ± 15.4%. Conclusion: The localized spine shim offers a promising new means of correcting magnetic field distortion in the spinal cord. Magn Reson Med 76:1604–1611, 2016. © 2016 International Society for Magnetic Resonance in Medicine